2013
DOI: 10.1590/0103-6440201302238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PDGF-BB, IGF-I Growth Factors and their Combination Carried by Liposomes in Tooth Socket Healing

Abstract: This work evaluated the bone-forming potential of the platelet-derived growth factor isoform BB (PDGF-BB), insulin-like growth factor I (IGF-I), and mixed PDGF-BB/IGF-I delivered in liposomes compared with phosphate buffered saline (PBS), in the healing process of rat tooth sockets. One hundred and twelve Wistar rats were randomized into 7 groups of 16 animals each and were evaluated at 3, 7, 14 and 21 days after extraction of the maxillary second molars. The left sockets were treated with PBS (P), empty lipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Furthermore, few studies showed that growth factors (such as PDGF‐BB, IGF‐1, TGF‐β 1) carried by liposomes, either in isolated forms or associated forms, can enhance post‐extraction alveolar bone repair (Abreu, Ferreira, Silva, Paulo Cde & Miziara, ; Ferreira, Abreu, Silva, Silveira & Barreto, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, few studies showed that growth factors (such as PDGF‐BB, IGF‐1, TGF‐β 1) carried by liposomes, either in isolated forms or associated forms, can enhance post‐extraction alveolar bone repair (Abreu, Ferreira, Silva, Paulo Cde & Miziara, ; Ferreira, Abreu, Silva, Silveira & Barreto, ).…”
Section: Resultsmentioning
confidence: 99%
“…IGF-1 plays an important role in bone growth and development [ 32 , 33 ] and promotes cell proliferation and osteogenic differentiation in HPDLs [ 20 , 24 ]. In addition, the in vitro study demonstrated that IGF-1 is a growth factor that responds early to mechanical stress [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…IGFs consist of several family members such as IGF-1 and IGF-2 [ 19 ]. IGF-1 plays a role in various cellular activities, including survival, proliferation, and differentiation [ 20 26 ]. IGF-1 is involved in several kinds of cells and tissues [ 19 ] while IGF-2 plays an important role mainly during prenatal development [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The production of osteocalcin and vascular endothelial growth factor has confirmed the enhancement in repair of socket bone (Abreu et al 2013). Liposome encasing buflomedil hydrochloride has been topically applied to wounds in normal and ischemic mice.…”
Section: Tissue Regenerationmentioning
confidence: 90%